Four-year dynamic observation and study on standardized management of elderly patients with type 2 diabetes in Beijing Yongding Road Community. Issue 2 (1st June 2014) - Li, Yue; Shen, Dongyun; Zhang, Wei; Wang, Yimin; Li, Hongmei; Geng, Jie; Yang, Liying; Xiao, Zhijun; Liu, Yan; Feng, Zhigang; Cao, Linying; Jin, Yan; et al.
Abstract : Purpose: This study aimed to understand the joint standard of blood glucose, blood lipids, and blood pressure in elderly patients >60 years of age with type 2 diabetes in the Beijing Yongding Road Community. Methods: One hundred ninety-two elderly patients >60 years of age who were diagnosed with type 2 diabetes in Yongding Road Community served as the investigation subjects, underwent standard management, and the dynamic changes in blood glucose, blood lipids, and blood pressure were monitored for 48 months. Results: At the end of the observation period, the standard rates of fasting blood glucose and postprandial blood glucose were 72.55% and 80.00%, respectively, which were increased compared with 55.73% and 56.08% at baseline ( P <0.01). The standard rate of HbA1c was 59.81%, which was increased compared with 53.44% at baseline ( P >0.05). The standard rates of TG and LDL-C were 76.71% and 60.38%, respectively, which were increased compared with 54.69% and 34.74% at baseline, and the standard rate of HDL-C was 13.64%, which was decreased compared with 40.10% at baseline ( P <0.01). The standard rate of BP was 58.33%, which was increased compared with 38.54% at baseline ( P <0.01). The optimal control rate of blood glucose for 48 months (the standard times of the total measurement times in 48 months ≥75%) was higher; the fasting blood glucose was 52.17%, the 2-h postprandial blood glucose was 60.22%, and the HbA1c was 46.45%. The optimal control rate of blood lipids was lower; LDL-C was 17.49% and HDL-C was 13.59%. The optimal control rate of BP was 9.13%. At the end of the observation period, the levels of fasting blood glucose and postprandial blood glucose were decreased by 0.7 mmol/L and 1.48 mmol/L, respectively, compared with the baseline ( P <0.01). The level of HbA1c was decreased by 0.18% compared with the baseline ( P <0.05). The levels of LDL-C and HDL-C were decreased by 0.4 mmol/L and 0.23 mmol/L, respectively, compared with the baseline ( P <0.01). The levels of SBP and DBP were decreased by 4 mmHg compared with the baseline ( P <0.01). At the end of the observation period, the joint standard rate of the three indices of HbA1c, LDL-C, and BP was 24.72%, which was increased compared with 6.25% at baseline ( P <0.01). Conclusion: Standardized management of elderly patients with diabetes in the Community can improve the joint standard rate of blood glucose, blood lipids, and blood pressure. The optimal control rate and joint standard rate are the important indices for evaluating the quality of diabetes management.